Nilai-Nilai Moral dalam Novel Yang Fana Adalah Waktu Karya Sapardi Djoko Damono dan Implikasinya Terhadap Pembelajaran Teks Novel - Kadriani, Anisa; Asmawati; Hendri, Bunga Febrimora (Global Action and Education for Society, 2023)
This study aims to describe the following two things. First, to describe the moral values ​​contained in the novel Yang Fana Is Time by Sapardi Djoko Damono. Second, the implication of moral values ​​in the novel Yang Fana Is Time by Sapardi Djoko Damono. This type of research is a qualitative research using content analysis method. The data source in this research is the novel Yang Fana Is Time by Sapardi Djoko Damono. The research instrument is the researcher himself. The data collection technique in this study was a reading and note-taking technique using three formats: the first, the data identification format for the characters and characterizations, the second, the background data inventory format and the plotting stages, and third, the classification of the data on moral values ​​in the novel Yang Fana Is Time. by Sapardi Djoko Damono. There are three analytical techniques used in this study, namely (1) data reduction, (2) data presentation, (3) data verification. The data validation technique used in this study is the investigator triangulation technique. Based on the findings in the analysis of the novel Yang Fana Is Time by Sapardi Djoko Damono, they are as follows: first, it describes the moral values ​​in the novel Yang Fana is Time by Sapardi Djoko Damono. (1) the value of honesty, (2) the willingness to be responsible, (3) the moral value of moral independence. Of the three moral values ​​above, the most dominant found in this study are the values ​​of honesty. Second, the implications of this research are applied in the learning of novel texts, especially in the Student Worksheet (LKPD).